Exploration of collagenase, cyclooxigenases, angiogenesis and free radical processes as the putative pharmacological targets of Arum maculatum L. Issue 1 (1st January 2020) - Kochmarov, Vladimir; Marinov, Lyubomir; Kozuharova, Ekaterina; Hristova-Avakumova, Nadya; Hadjimitova, Vera; Traykov, Trayko; Biljali, Sefedin; Nuhiu, Nexhibe; Benbassat, Niko; Momekov, Georgi
Abstract: In line with the well-established ethnobotanical use of Arum maculatum for the treatment of hemorrhoidal disease, we sought to determine the activities of 30% or 70% ethanol extracts of the plant tubers in an array of pharmacological and biochemical models of some crucial events implicated in the pathogenesis of this disorder, namely angiogenesis, collagenase activity remodeling, cyclooxygenase activity, IL-2 secretion and oxidative stress. The tested hydro-alcoholic extracts from A. maculatum tubers inhibited the proliferation of EA.hy926 vascular endothelial cells, but even at the highest administered concentrations no decrease in viability was observed. The extracts induced a concentration-dependent decrease in collagenase activity, whereby the effects were more pronounced at the lower concentration of ethanol in the extragent. Moreover the tested extracts induced concentration-dependent suppression of cyclooxygenase activity (COX-1 and 2), albeit at very high and presumably supraphysiological concentrations. The extracts augmented the PHA/PMA-induced secretion of IL-2 from Jurkat E.6 (human T-cells), which was more pronounced following exposure to the 30% ethanol-derived product. The 30% EtOH extract demonstrated anti-radical properties against both stable free radicals (ABTS and DPPH) and biologically relevant reactive oxygen species (ROS), which could be considered as important mediators of inflammation and signaling molecules. Our findings give us reason to conclude that the hydroalcoholic extracts of A. maculatum tubers possess anti-inflammatory, antiangiogenic and antioxidant effects which in concert could contribute to its efficacy for the management of hemorrhoidal disease.